Efeitos hipolipemiante e antioxidante do extrato etanólico da casca do fruto da Annona crassiflora Mart. e seus polifenóis em camundongos hiperlipidêmicos induzidos por Triton WR-1339 (tiloxapol) - Ramos, Letícia Pereira Afonso (2020)
Dyslipidemia is a risk factor for the pathogenesis of several diseases, such as obesity, hypertension, atherosclerosis and cardiovascular diseases. Furthermore, to interfering with serum cholesterol and triglyceride concentrations, hyperlipidemia is involved in increasing oxidative stress and decreasing antioxidant defenses. In this context, medicinal plants have shown antioxidant properties that could support in reversing the deleterious effects caused by the excess of free radicals. Annona crassiflora Mart., popularly known as araticum, is a plant native to the cerrado rich in bioactive compounds. Although underexplored, studies have shown that A. crassiflora has polyphenols with relevant characteristics in the modulation of the lipid profile, anti-atherosclerotic, anti-inflammatory and anti-hepatoxic action. The current study was conducted to evaluate the hypolipidemic and antioxidant effects of the ethanol extract and the polyphenolic fraction in ethyl acetate of the Annona crassiflora Mart. fruit peel in C57BL/6 male Triton WR-1339 (400 mg/kg) induced hyperlipidemic mice. The animals were pre-treated for 12 days with three different doses (10, 30 and 100 mg / kg) of ethanolic extract (EtOH) from A crassiflora Mart., as well as the fraction of this plant in ethyl acetate (AcEt) and the purified fraction of proanthocyanidins (PCND). The intraperitoneal injection of tiloxapol to induce dyslipidemia was performed on the 13th day, resuming treatment with the bioactive compounds after 26 hours. Blood and feces samples were collected periodically to assay the animals' lipid profile. The liver was the chosen organ for analyzing parameters of oxidative and metabolic stress in the groups. The results showed that the bioactive compounds from the araticum were not able to normalize the levels of TG, CT and non-plasma HDL-C, but increased HDL-C levels considerably, compared to the control group. In the liver and feces, there was a reduction in TG and CT levels with EtOH. The extract and the fractions reduced lipid peroxidation (TBARS) and the AcEt and PCND fractions reduced the content of carbonylated proteins in the liver. Although the antioxidant capacity (FRAP) was not changed between the groups, the total sulfhydryls in the liver were higher with 30 mg/kg of the AcEt fraction and, still the antioxidant enzymes SOD and CAT were increased in the lowest doses (10 and 30 mg/kg) of EtOH in relation to the naive. These findings suggest that A. crassiflora polyphenols extracted in ethanolic solvent and ethyl acetate, seem to have some important antioxidant and hepatoprotective properties even in an acute experimental model and that isolated PCNDs do not have the same potential under these conditions.